(untitled) (Revista Brasileira de Contabilidade e Gestão, 2020)
This paper enhances the theoretical pluralism of Strategic Management and aims to show its construction as a scientific field of different approaches, fighting for recognition and acceptance. The theoretical basis discuss Pierre Bourdieu’s contribution about scientific field, from which are analyzed eleven Theories of Strategic Management. Among the dominant positions in the field, highlighted the contributions of the Economic Base Theories; between the beginners, there are the Behavioral Base Theories, especially Strategy as Practice Theory. It was not realized scientific revolution in the field, but an incremental process of evolution of the knowledge.